Antibiofilm activity of neem leaf (Azadirachta indica A. Juss) ethanolic extracts against Enterococcus faecalis in vitro - Suhartono Suhartono; Cut Soraya; Putri Shabira (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Enterococcus faecalis commonly infects root canals by forming a biofilm. Extracts from neem leaves (Azadirachta indica A. Juss) have been shown to have antibacterial properties, indicating their potential in preventing or treating biofilm formation caused by bacteria. Purpose: This study aims to investigate the phytochemical compounds present in neem leaves (Azadirachta indica A. Juss) and establish the concentration of ethanol-based neem leaf extract that can effectively inhibit the in vitro growth of Enterococcus faecalis biofilm. Methods: This study employed the maceration technique for extraction, gas chromatography mass spectroscopy for the analysis of plant chemicals, and a microtiter plate assay for measuring biofilm formation with treatment concentrations of 6.25%, 12.5%, 25%, 50%, and 75%, with a positive control of 0.2% chlorhexidine. Results: A phytochemical analysis revealed that the ethanol extract of neem leaves contained 22 different metabolites, mainly terpenoids and fatty acids. The extract demonstrated antibiofilm activity only at a concentration of 12.5% with an average biofilm inhibition of 36.85%. However, lower concentrations of 6.25%, 25%, 50%, and 75% had the opposite effect, promoting biofilm formation in Enterococcus faecalis. Conclusion: Phytochemical metabolite contained in the ethanolic extracts of neem leaves might contribute a promising agent in treating a biofilm-mediated root canal infection of Enterococcus faecalis.